2017
DOI: 10.1177/1359105317712575
|View full text |Cite
|
Sign up to set email alerts
|

Representations and experiences of well-being among diabetic adolescents: Relational, normative, and identity tensions in diabetes self-management

Abstract: We explore representations of well-being in adolescents with Type 1 diabetes in order to better understand their expectations and needs in therapeutic patient education. In total, 28 interviews were performed and then submitted to thematic content analysis and lexicometric analysis. Results show the intervention of psychosocial processes in the relationship that adolescents maintain with well-being and self-management. More specifically, we observed that well-being is impacted by areas of tension between the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Fonte et al studied representations of well-being among adolescents in relation to diabetes management. They suggested that some adolescents may perceive self-management as an obstacle to well-being because they think it is associated with an adult identity, which is incompatible with preserving a kind of socialization that underpins their adolescent identity [38]. Thus, according to Fonte et al (2019), adolescents see a discrepancy between diabetes self-care and life as a young person.…”
Section: Managementmentioning
confidence: 99%
“…Fonte et al studied representations of well-being among adolescents in relation to diabetes management. They suggested that some adolescents may perceive self-management as an obstacle to well-being because they think it is associated with an adult identity, which is incompatible with preserving a kind of socialization that underpins their adolescent identity [38]. Thus, according to Fonte et al (2019), adolescents see a discrepancy between diabetes self-care and life as a young person.…”
Section: Managementmentioning
confidence: 99%
“…Le Figaro vs. L'Humanité), the type of newspaper (national vs. regional), and the geographical base of the newspaper (Atlantic coast vs. Mediterranean coast vs. Channel coast vs. France in general). We adopted a triangulation approach in which computer-assisted analysis was interpreted and then content analysed (see Fonte et al, 2017): following the DHC, we started by identifying the different lexical classes, the main ideas, words and variables associated with them. Secondly, within each lexical class we conducted a content analysis, from which sub-themes were identified.…”
Section: Capacity To Associate Lexical Classes With Contextual Variables (Metadata)mentioning
confidence: 99%
“…Following on from previous studies in the French context (see Colson et al, 2016b; Fonte et al, 2019), this article aimed to better understand the construction of the climate of trust that adolescents maintain with their parents and professionals in the context of therapeutic education. On the basis of the three spheres of belonging of social representations (Jodelet, 2012), our objectives consisted in the following:…”
Section: This Studymentioning
confidence: 99%